If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -4) + 5 = x + -15 Reorder the terms: 3(-4 + x) + 5 = x + -15 (-4 * 3 + x * 3) + 5 = x + -15 (-12 + 3x) + 5 = x + -15 Reorder the terms: -12 + 5 + 3x = x + -15 Combine like terms: -12 + 5 = -7 -7 + 3x = x + -15 Reorder the terms: -7 + 3x = -15 + x Solving -7 + 3x = -15 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -7 + 3x + -1x = -15 + x + -1x Combine like terms: 3x + -1x = 2x -7 + 2x = -15 + x + -1x Combine like terms: x + -1x = 0 -7 + 2x = -15 + 0 -7 + 2x = -15 Add '7' to each side of the equation. -7 + 7 + 2x = -15 + 7 Combine like terms: -7 + 7 = 0 0 + 2x = -15 + 7 2x = -15 + 7 Combine like terms: -15 + 7 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| 10-6n=-14 | | -3*x=6 | | y=-10/5+1 | | 10-6n=-4 | | m^4-5m^3+7m^2-3m=0 | | 6-(4x-2)=3-5x | | 2xy-xz=0 | | x+(-3)=-14 | | 2x^2-28x-64=0 | | 3x+5x=7x+9 | | -6+7x=0 | | 10y+6=8y-8 | | ln(-6+7x)=0 | | 3x^2+13x+22=0 | | 3(2a+15)-8a=-11 | | 6x-6=4x+42 | | 3(x+3)=-15 | | 50x^3+175x^2-8x-28=0 | | 45-2x=x+30 | | mn+16=4 | | 5x^2-120=5 | | 3(4x+8)=9x+12 | | 45-3x=-8x | | -2(-2b+5)8b=14 | | m+16=4 | | y=3(-24)-6 | | x^2+14x-5k+4k^3+1=0 | | -27=x^4-12x^2 | | -6x+9y=-6 | | 11-(23m-10)=5(4-m) | | 6g+3(-5+4g)=1-g | | (90000*0.5326-5150)/1000*31.91= |